2014
DOI: 10.1097/iae.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study on the Incidence of Rhegmatogenous Retinal Detachment in Denmark, With Emphasis on the Risk of the Fellow Eye

Abstract: Patients with RRD on the first eye have a 100 times greater risk of developing RRD on the second eye, and the risk increases with male gender and surgery on the lens but decreases with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 41 publications
9
59
2
5
Order By: Relevance
“…The validation of the NPR has been noted in a previous paper (Hajari et al. ). It showed that the NPR has a registration error of 0.36–3% and is thereby a valid register to use in epidemiological studies.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…The validation of the NPR has been noted in a previous paper (Hajari et al. ). It showed that the NPR has a registration error of 0.36–3% and is thereby a valid register to use in epidemiological studies.…”
Section: Methodsmentioning
confidence: 76%
“…The study has some disadvantages, which have been discussed in a previous paper concerning data from the same registry (Hajari et al. ). Some of the disadvantages we previously have discussed are as follows: Assuring that no treatment has been conducted prior to the 5‐year lead period to ensure the initial operation is a primary RRD. Missed cases due to our search strategy. Lack of any clinical data in the register. …”
Section: Discussionmentioning
confidence: 99%
“…; Hajari et al. ). Our results showed a predominance of males in the ratio of retinal detachments (approximately 1.8:1).…”
Section: Discussionmentioning
confidence: 97%
“…Männer sind mit einer Ratio von 1,3:1 bis 2,3:1 (m:w) häufiger von rhegmatogenen Netzhautablö-sungen betroffen als Frauen [13, 16,17,19,25,26]. Einzelne Untersuchungen wiesen jedoch ein häufigeres Auftreten bei Frauen in der phaken nichttraumatischen Gruppe (Ratio m:w = 1,14:1,4) auf [14,18].…”
Section: Geschlechtunclassified
“…In den letzten Jahren finden sich nationale Registerstudien aus dem Vereinigten Königreich als auch aus Dänemark, bei denen eine systematische digitale Erfassung der durchgeführten Leistungen, Komplikationen und Folgeoperationen durchgeführt worden ist [26,54,55,56,57,58] [58]. Das größte Risiko der Entstehung einer pseudophaken Netzhautablösung wird in den ersten 6 Monaten nach der Operation beobachtet und flacht danach ab, bleibt aber sogar 10 Jahre nach der Kataraktoperation weiterhin erhöht.…”
Section: Kataraktoperationunclassified